PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KARAKTER SISWA DALAM PPKN - Kiftiyah, Millatul; Anggraeni, Ekaliya Priti; Rochmadi, Nur Wahyu (Prosiding Temu Ilmiah Nasional Guru, 2023)
Memorable education for students is learning that is able to build basic concepts of thinking worthy of the phenomena of the environment around students. A decent learning atmosphere will support the learning process to be student-oriented and centered. The selection of learning models that are based on learning objectives will have a positive impact. With the Guided Inquiry learning model, students will engage in active behavior to understand concepts by PPKN subjects. So that it can form students who think logically, are disciplined, curious, independent, honest, and responsible. This shows that the Guided Inquiry learning model can develop student character. This study aims to identify the Guided Inquiry learning model for student character in the PPKN subject. Starting from planning to evaluation using research methods, qualitative research methods, and library research, known as literature research in the form of books, articles, journals, past and present that support theory. The results showed that the Guided Inquiry learning model on student character in the PPKN was creative and effective in the learning process. The Guided Inquiry learning model can be an alternative model applied to the learning process.